Assim nasce uma igreja: a multiplicação das comunidades cristãs independentes no município da Serra, Estado do Espírito Santo - Stephanini, Valdir (2010)
Thus was born a church: the rise of the Christian Independent communities in the city of Serra, Espírito Santo is a work that aims to identify the factors that has triggered the birth of new Christian churches, not related to historical communities in the municipality of Serra, as well as the impact of this phenomenon in Historical Protestant Churches, especially in Baptist Churches, in both its benefits and the losses. In the first chapter, the geographical search is located and theoretically, through a mapping of the religious city of Serra and a presentation of the typology used in this work. The second chapter provides a brief history, showing how the Christian churches were born from the New Testament period to the present, with emphasis on early Christianity Churches, Great Schism, the Reform Movement of the XVI century, and in the Pentecostal movement. The third chapter identifies the external and internal factors that have triggered the birth of new churches. The fourth chapter presents the benefits and losses that the fragmentation of Christianity creates to the Historic Christian Churches and the Kingdom of God.